Factors influencing drug-susceptible tuberculosis treatment outcomes in Romania and Ukraine - Ioana Margineanu; Fajri Gafar; Teodora Butnaru; Dragos Baiceanu; Raluca Dragomir; Ihor Semianiv; Florin Mihaltan; Ioana Munteanu; Beatrice Mahler; Liliia Todoriko; Sorina Margineanu; Ymkje Stienstra; et al. (PLoS ONE, 2025)
Background Tuberculosis (TB) remains one of the most globally impactful infectious diseases, with a recorded mortality of 1.6 million in 2022. In Romania and Ukraine, two high burden countries in the context of the WHO European region, treatment is geared towards cure; however, this path is paved with significant challenges, from morbidity to loss to follow-up. Methods A retrospective study was performed for drug-susceptible TB patients hospitalised in three TB expertise centres in Romania and Ukraine using routinely collected data. Univariable and multivariable logistic regression analyses were used to assess predictors of three treatment outcomes: unfavourable outcomes, loss to follow-up, and death. Results A total of 838 patients diagnosed with drug-susceptible TB were included. Median hospitalisation was 39 days (IQR 25–67), and treatment duration was 7 months (IQR 6–8). Predictive variables differed by outcome. For unfavourable outcomes, the multivariable model included age > 65 years, chronic kidney disease, at least one cavity on chest X-ray, underweight status, and persistently abnormal laboratory parameters despite intervention. Independent predictors of loss to follow-up were alcohol use, COPD, TB infection within two years prior to admission, obesity, slow treatment response, and sputum microscopy ≥2 + . Predictors of death included age > 65 years, male sex, cirrhosis, chronic kidney disease, underweight status, persistently abnormal laboratory parameters, and slow treatment response. Conclusion Contextualising factors influencing drug-susceptible TB treatment outcomes in different settings can support the development of tailored interventions that enable early identification of patients at higher risk, thereby avoiding unnecessary treatment effects.